THE ROLE OF LSF INTERNAL MEDIA IN DISTRIBUTING INFORMATION ON THE GNBSM PROGRAM TO STAKEHOLDERS - Sartika Dewi, Yuli; Aisya Putri, Delvina; Pradhana Sumbodo, Yama (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Film Censorship Institute is an institution that carries out the task of determining the appropriate position for cinema films, television, soap operas and advertisements in Indonesia. Film or television show can only be screened if it is declared censored by the LSF. As a communication medium, film is a form foundation for educating the nation's, developing self-potential, fostering noble character, promoting public welfare, promotional platform to be protected from negative content that is inconsistent with Pancasila ideology. Therefore LSF emphasizes media literacy. Since September 2021, LSF has published GNBSM, which is a movement that has been developed by LSF so that people are proficient in choosing and sorting shows according to age classification. LSF expected to be able to synergize with stakeholders. Analytical method is a qualitative method, study uses observation and interview methods conducted by interviewing respondents from the LSF, Chair of the Appreciation and Promotion Sub-Commission, Chair of the Legal and Advocacy Sub-Commission, Chair of the Commission III, Secretary of Commission III. From the results of this study it was found that the internal media used by LSF in disseminating the GNBSM program to stakeholders were print media as magazines, social media as Instagram, Facebook, TikToK, Twitter, Youtobe.